Using Erasure Codes to Overcome Reliability Issues in Energy-Constrained Sensor Networks - Mutschlechner, Margit; Li, Bijun; Kapitza, Rüdiger; Dressler, Falko (Proceedings of the 11th IEEE/IFIP Conference on Wireless On demand Network Systems and Services (WONS 2014), 2014)
We study the use of Erasure Codes (ECs) for transmitting information from mobile sensor nodes to stationary base stations. In particular, we are interested in improving the overall communication reliability of the wireless communication. Our scenario is wildlife monitoring in which bats are equipped with tiny sensor nodes, just being capable to store a few kB of data and to exchange information over a wireless communication link. This link is used, on the one hand, for determining contact times between individuals. On the other hand, these contacts are communicated in aggregated form to stationary base stations. Since the channel quality may vary quickly due to the continuous movements of bats and the heterogeneous environment, the communication is in general assumed to be highly unreliable. Conventional reliability improving approaches such as full data replication or on-demand retransmission are too expensive or even not possible due to very strict energy constraints and asymmetric channels. ECs allow to enhance the reliability of data transmissions by transmitting redundant data. In this work, we investigate the trade-off between reliability achieved and the cost in form of additional transmissions, i.e., the additional energy costs. Our results clearly show that ECs improve the communication reliability considerably with almost no impact on the resulting delay. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD4.usinge_0